2020
DOI: 10.1152/ajprenal.00330.2019
|View full text |Cite
|
Sign up to set email alerts
|

A model of mitochondrial O2consumption and ATP generation in rat proximal tubule cells

Abstract: Oxygen tension in the kidney is mostly determined by O2 consumption (Qo2), which is, in turn, closely linked to tubular Na+ reabsorption. The objective of the present study was to develop a model of mitochondrial function in the proximal tubule (PT) cells of the rat renal cortex to gain more insight into the coupling between Qo2, ATP formation (GATP), ATP hydrolysis (QATP), and Na+ transport in the PT. The present model correctly predicts in vitro and in vivo measurements of Qo2, GATP, and ATP and Pi concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 99 publications
(107 reference statements)
1
22
0
Order By: Relevance
“…The PT accounts for two thirds of sodium reabsorption by the kidney, done mostly via active transport [51]. The work of Edwards et al [17] that we build on here suggests that the efficiency of cellular respiration in the kidney is reduced by diabetes, suggesting that could be a cause of diabetic nephropathy. Furthermore they suggest that a class of diabetes medications that target the kidney, SGLT-2 inhibitors, could worsen the nephropathic effects of diabetes.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The PT accounts for two thirds of sodium reabsorption by the kidney, done mostly via active transport [51]. The work of Edwards et al [17] that we build on here suggests that the efficiency of cellular respiration in the kidney is reduced by diabetes, suggesting that could be a cause of diabetic nephropathy. Furthermore they suggest that a class of diabetes medications that target the kidney, SGLT-2 inhibitors, could worsen the nephropathic effects of diabetes.…”
Section: Introductionmentioning
confidence: 82%
“…There are three classes of question that we wish to address in this work. First, the comparative questions: a published in silico study on PT mitochondrial function has found that oxygen tension is not rate limiting in the renal cortex for ATP production [17], we compare this to the outer medulla, where lower baseline oxygen tension means that hypoxia may be more extreme. And relatedly, in line with the predictions of Zhang and Edwards [88] that ATP production should be more efficient in the mTAL, we wish to consider the ratios of ATP Synthase mediated ATP generation to Complex IV mediated oxygen consumption, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these models can potentially be improved by data regarding these processes, including new information being generated from models of mitochondrial function in the kidney. 99…”
Section: How Does Reduced Nephron Mass Affect Kidney Oxygenation?mentioning
confidence: 99%
“…However, these model predictions will presumably be highly influenced by the efficiency of oxygen utilization for sodium resolution in these kidneys, including how this efficiency varies locally within tissue in pathological states. Thus, these models can potentially be improved by data regarding these processes, including new information being generated from models of mitochondrial function in the kidney …”
Section: Renal Oxygenation: What Are the Critical Questions Mathematimentioning
confidence: 99%